Enhancing Physical and Cognitive Efficiency in Elderly Individuals at Risk for Dementia Using Whole-Body Electrostimulation: A Randomized Controlled Trial - Marco Centorbi; Giulia Di Martino; Carlo Della Valle; Andrea Buonsenso; Giuseppe Calcagno; Giovanni Fiorilli; Alessandra di Cagno (Journal of Functional Morphology and Kinesiology)
Objective: The aim of this randomized controlled trial (RCT) was to assess the impact of a 12-week intervention of two 20-min sessions per week, combining aerobic exercise with whole-body electromyostimulation (WB-EMS), on physical and cognitive performance in the elderly. Methods: A total of 61 participants (age = 71 ± 5.64 years), healthy or at risk for dementia, were randomly assigned to an experimental training group (ETG, n = 33) and a control group (CON, n = 28). Participants underwent 20-min aerobic training sessions, with intensity increasing from 60% to 80% of heart rate reserve (HRR), with and without continuous WB-EMS stimulation (35 Hz, 350 μs). Results: Significant time/effects for both the ETG and CON were found in the physical performance tests, with significant time*group interactions favoring the ETG for the arm curl test (p < 0.001) and the sit-to-stand test, with significant differences between groups (p = 0.001), as well as for the hand grip test (p < 0.001) and the 6-min walking test (p < 0.001), with significant time*group interactions (p = 0.003). Both groups improved their performance on the soda pop test (p < 0.001). ETG outperformed CON in memory performance (PROSA, p = 0.046; RAVLT immediate recall, p < 0.001) and on selective attention and visuospatial processing (attention matrices, p = 0.014). Some cognitive tests showed no significant improvement, likely due to the short intervention period for cognitive function (MMSE, p = 0.628; TMT, p = 0.698; Stroop error, p = 0.188) or memory performance (PROSA, p = 0.338). Conclusion: The absence of decline suggests a protective effect of physical activity. WB-EMS, combined with aerobic training, enhances the benefits of physical activity and helps counteract cognitive decline in older adults.